The adaptive method of threshold image processing - Bilynskyi, Y. Y.; Krysak, T. M.; Klymenko, I. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The adaptive method of threshold image processing is offered in the paper, it allows automatically to determine threshold value as a result of approximation of the three-peak diagram's section that indicates the adaptive character and allows to use it not only for threshold processing, but also for edge detection of the image.